2019
DOI: 10.1136/ijgc-2019-000383
|View full text |Cite
|
Sign up to set email alerts
|

Accessory polar renal artery not pre-operatively visualized at extra-peritoneal para-aortic lymphadenectomy

Abstract: The objective of this video is to describe the technique of extra-peritoneal para-aortic laparoscopic lymphadenectomy and emphasize potential vascular risks that should be taken into account during the procedure.The procedure was performed at Donostia University Hospital, a tertiary referral and educational center in San Sebastián, Spain.A 58-year-old woman, body mass index 25.4 kg/m2, G2P2, with a diagnosis of intermediate-risk endometrial adenocarcinoma, International Federation of Gynecology and Obstetrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The woman had no postoperative complications [52]. Although oncogynecologists often described additional RAs during PALND, the real incidence of injury is unknown [53,54]. However, all authors concluded that surgeons should be familiar with these potential anatomical variations .…”
Section: Surgical Considerationsmentioning
confidence: 96%
“…The woman had no postoperative complications [52]. Although oncogynecologists often described additional RAs during PALND, the real incidence of injury is unknown [53,54]. However, all authors concluded that surgeons should be familiar with these potential anatomical variations .…”
Section: Surgical Considerationsmentioning
confidence: 96%
“…Retroperitoneal enlarged lymph nodes above the renal vessels and in the vicinity of the celiac axis may be considered difficult sites to resect. Furthermore, vascular anomalies, such as a retro-aortic left renal vein, a double vena cava or left vena cava, or an adjunctive renal artery (Figure 3), may be visualized in the pre-operative imaging and, when reported, may help to decrease the risk of operative and post-operative complications such as abnormal bleeding, renal injury, and partial renal necrosis 11. Omental deposits are common in ovarian cancer patients and their detection on imaging studies is not a major challenge.…”
Section: Introductionmentioning
confidence: 99%